Transcriptome and Metabolome Analyses of the Flowers and Leaves of Chrysanthemum dichrum - Liu, Hua; Chen, Xiaoxi; Chen, Hạixia; Lu, Jie; Chen, Dongliang; Luo, Chang; Cheng, Xi; Jia, Yin; Huang, Conglin (Frontiers in Genetics, 2021)
Chrysanthemum dichrum is an important wild species in the family Asteraceae. However, because of a lack of genetic information, there has been relatively little research conducted on the molecular mechanisms in C. dichrum. There is no report describing the transcriptome and metabolome of C. dichrum flowers and leaves at different developmental stages.In this study, high-throughput sequencing and RNA-seq analyses were used to investigate the transcriptome of C. dichrum leaves, flower buds, and blooming flowers. Additionally, these three tissues also underwent a metabolomics analysis. A total of 447,313,764 clean reads were assembled into 77,683 unigenes, with an average length of 839 bp. Of the 44,204 annotated unigenes, 42,189, 28,531, 23,420, and 17,599 were annotated using the Nr, Swiss-Prot, KOG, and KEGG databases, respectively. Furthermore, 31,848 differentially expressed genes (DEGs) were detected between the leaves and flower buds, whereas 23,197 DEGs were detected between the leaves and blooming flowers, and 11,240 DEGs were detected between the flower buds and blooming flowers. Finally, a quantitative real-time Polymerase Chain Reaction(qRT-PCR) assay was conducted to validate the identified DEGs. The metabolome data revealed several abundant metabolites in C. dichrum leaves, flower buds, and blooming flowers, including raffinose, 1-kestose, asparagine, glutamine, and other medicinal compounds.The expression patterns of significant DEGs revealed by the transcriptome analysis as well as the data for the differentially abundant metabolites in three C.dichrum tissues provide important genetic and metabolic information relevant for future investigations of the molecular mechanisms in C. dichrum. Moreover, the results of this study may be useful for the molecular breeding, development, and application of C. dichrum resources.